It Takes a Village: How Community-Based Peer Support for Breastfeeding Bolsters Lactation Prevalence Among Black Mississippians on the Gulf Coast - John P. Bartkowski; Katherine Klee; Xiaohe Xu; Jacinda B. Roach; Shakeizia (Kezi) Jones (Pediatric Reports)
Background/Objectives: Breastfeeding rates are considerably lower among African American women and across the U.S. South. Our study introduces the concept of community-based peer support for breastfeeding, as measured through beliefs about women’s comfort breastfeeding in various social situations (i.e., in the presence of women and men as well as close friends and strangers). Methods: We examine if community-based peer support for breastfeeding is associated with reported lactation prevalence in primary social networks among survey respondents living on the Mississippi Gulf Coast. Special attention is paid to racial differences in the breastfeeding support–prevalence relationship. We use data drawn from a survey that combines a random sample of adults who are representative of the Mississippi Gulf Coast population and a non-random oversample of African Americans in this predominantly rural tri-county area. Results: Analyses of data from wave 1 of the CDC-funded 2019 Mississippi REACH Social Climate Survey reveal low overall levels of African American breastfeeding network prevalence (knowing friends and family who have breastfed). However, community-based peer support for breastfeeding significantly amplifies breastfeeding network prevalence for black Mississippians when compared with their white counterparts. Discussion: Previous research has indicated that breastfeeding promotional messages have a limited impact on African American breastfeeding propensity along the Mississippi Gulf Coast. However, the current study indicates that enhanced community-based peer support for breastfeeding can be a key facilitator for improved lactation outcomes among African Americans as compared with whites. Conclusion: We establish that breastfeeding is best conceived as both an interpersonal encounter (an activity often conducted in the presence of others) and a collective achievement (a practice influenced by community norms). We discuss study implications and directions for future research.